Study of the cardiovascular system's reaction to the training load of highly qualified wrestlers - Burnashev, R. A. (International Journal of Wrestling Science, 2023)
This study examined the reaction of the cardiovascular system of highly qualified freestyle wrestlers to a competitive load in the pre-competitive period of training, where such internal changes such as the maximum heart rate, heart rate variability before and after the load, the level of stress before and after the load, and the recovery time of athletes after exercise in the submaximal and maximum intensity zones. The heart rate and stress index were measured before the load at rest, during the competitive load and after the completion of the training process, the most wrestlers before the start of the training process, which subsequently had a negative impact on the entire training process. In this connection, it was decided to identify the causes causing an increase in the stress of athletes. The results of the study discussed in this article may be useful to coaches and specialists in the preparation of athletes in martial arts. Purpose of the research. To reveal the maximum heart rate for the competitive load in highly qualified wrestlers in the pre-competitive period of preparation. Subjects: 4 highly qualified wrestlers participated in the study (2 wrestlers participated in the Olympic Games in Tokyo, 1 wrestler was a bronze medalist of the Olympic Games in Buenos Aires and 1 wrestler was a bronze medalist of the Olympic Games in Rio de Janeiro). Methods: The study of the reaction of the cardiovascular system with an instrumental method, the identification of heart rate variability and stress index before exercise, during exercise and after it, as well as the recovery time with a special measuring device Veda Pulse and Polar h10 with CardrioMood software. The study lasted 4 microcycles, where each microcycle was 7 days. The training process was as follows: the athletes came to the gym, where, before the warm-up, we took measurements and determination of heart rate variability and stress index, then determined the maximum heart rate at submaximal and maximum load, as well as the performance of wrestlers. After the competitive load, the second measurement was carried out, where the heart rate variability and the stress index for the load were determined. Results of the study: as a result of the study, the following indicatorswere obtained. At the beginning of the training process, the average heart rate of highly skilled wrestlers was 74.8±6.7 beats per minute; during the submaximal training load, this indicator increased to 165.3±13.6 beats per minute. The submaximal load lasted 3 minutes. And in the maximum training load, the maximum heart rate reached 187.3±9.4 beats per minute. But to date, heart rate indicators in highly qualified athletes are uninformative, but heart rate variability and body stress index at high or low heart rate are more informative for coaches and specialists. Conclusions: In the course of the study of the cardiovascular system of the body of highly qualified freestyle wrestlers, it was revealed that at this stage the level of preparedness is not high enough to compete in the submaximal and maximum intensity zones to show high results in international competitions, and therefore it is necessary to further develop proposals and recommendations for increasing the special working capacity and the level of the functional state of athletes.